2014
DOI: 10.1007/s13181-014-0449-5
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Opioid Prescribing Practices for Chronic Pain: a 3-Year Analysis

Abstract: Chronic pain is a common reason for emergency department (ED) visits. Our objective was to describe opioid prescribing practices of ED providers when treating patients with chronic pain. We retrospectively evaluated opioid prescriptions from EDs at two tertiary care military hospitals. We queried the outpatient record database to obtain a list of opioid medications prescribed and ICD-9 codes associated with visits for chronic pain. We collected provider type and gender, number of pills, opioid type, and refill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…Substantial variation in opioid prescribing rates exists across emergency physicians (Barnett et al, 2017;Pomerleau et al, 2017;Tamayo-Sarver et al, 2014) and high prescribing ED providers have been linked to high rates of long-term substance use disorders among their patients (Tamayo-Sarver et al, 2014). Prior studies of ED opioid prescribing have been limited to a single state, the Medicare population (Varney et al, 2016), survey data (Tamayo-Sarver et al, 2004), or a small number of military hospitals (Ganem et al, 2015); have not included data more recent than 2011 (Kea et al, 2016;Mazer-Amirshahi et al, 2014a;Maughan et al, 2015;Pomerleau et al, 2016); have examined initiatives of limited scope (Barnett et al, 2017); or have examined only a cross-section of ED visits (Hoppe et al, 2015). Our study examined ED prescribing rates using a dataset with a large number of patients from commercial and Medicaid claims databases from multiple states over a period of more than a decade by patient demographic and clinical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial variation in opioid prescribing rates exists across emergency physicians (Barnett et al, 2017;Pomerleau et al, 2017;Tamayo-Sarver et al, 2014) and high prescribing ED providers have been linked to high rates of long-term substance use disorders among their patients (Tamayo-Sarver et al, 2014). Prior studies of ED opioid prescribing have been limited to a single state, the Medicare population (Varney et al, 2016), survey data (Tamayo-Sarver et al, 2004), or a small number of military hospitals (Ganem et al, 2015); have not included data more recent than 2011 (Kea et al, 2016;Mazer-Amirshahi et al, 2014a;Maughan et al, 2015;Pomerleau et al, 2016); have examined initiatives of limited scope (Barnett et al, 2017); or have examined only a cross-section of ED visits (Hoppe et al, 2015). Our study examined ED prescribing rates using a dataset with a large number of patients from commercial and Medicaid claims databases from multiple states over a period of more than a decade by patient demographic and clinical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these previous studies analyzed patients undergoing minor or outpatient orthopaedic operations, and have concluded that postoperative pain pill consumption is much lower (often <50%) than the number of pills dispensed. [7][8][9][10][11][12][13][14][15][16] Of the existing studies of opioid pain medication prescription and use in general surgery, most are retrospective in nature and use telephone surveys to gather data at one time point only. We sought to prospectively characterize postoperative opioid prescription practices and consumption at various time points in patients undergoing open and laparoscopic general surgery procedures on one surgical service and to assess patient satisfaction with post-discharge pain management.…”
mentioning
confidence: 99%
“…Tramadol fue el único opiáceo prescrito, a diferencia de otras publicaciones en que se prescribe mayormente oxicodona e hidrocodona 10 , este último no disponible en Chile. El uso inapropiado de opioides ha ido en aumento y está asociado a EA graves, como múltiples caídas, fracturas, readmisiones hospitalarias y muerte, especialmente en adultos mayores 6,7,11 . Es preocupante que más de la mitad de las prescripciones estudiadas tenía faltas de información en la dosis, duración del tratamiento, o ambos, más si los médicos en SU se encuentran entre los que más prescriben opioides 12 .…”
Section: Discussionunclassified